2013
DOI: 10.1038/ncomms3707
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and twistable non-volatile memory cell array with all-organic one diode–one resistor architecture

Abstract: Flexible organic memory devices are one of the integral components for future flexible organic electronics. However, high-density all-organic memory cell arrays on malleable substrates without cross-talk have not been demonstrated because of difficulties in their fabrication and relatively poor performances to date. Here we demonstrate the first flexible all-organic 64-bit memory cell array possessing one diode-one resistor architectures. Our allorganic one diode-one resistor cell exhibits excellent rewritable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(75 citation statements)
references
References 33 publications
(45 reference statements)
0
75
0
Order By: Relevance
“…In particular, high-performance flexible non-volatile memories based on various data storage principles such as resistive type [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] , flash 4,[25][26][27][28][29] and ferroelectric [30][31][32][33][34][35][36][37][38][39][40] hold great promise in a variety of emerging applications ranging from mobile computing to information management and communication. While the recent advances in this area are impressive, novel organic materials and electronic device structures that can be tightly rolled, crumpled, stretched, sharply folded and unfolded repeatedly without any performance degradation still need to be developed.…”
mentioning
confidence: 99%
“…In particular, high-performance flexible non-volatile memories based on various data storage principles such as resistive type [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] , flash 4,[25][26][27][28][29] and ferroelectric [30][31][32][33][34][35][36][37][38][39][40] hold great promise in a variety of emerging applications ranging from mobile computing to information management and communication. While the recent advances in this area are impressive, novel organic materials and electronic device structures that can be tightly rolled, crumpled, stretched, sharply folded and unfolded repeatedly without any performance degradation still need to be developed.…”
mentioning
confidence: 99%
“…In this regard, we designed a photonic flash memory device where IR light is used for data encryption in addition to an applied voltage bias. In flash memory device architecture, most of the organic or inorganic semiconductors have almost no absorption in the IR region due to their typical optical energy band gap [24][25][26][27][28] . Upconversion (UC) describes a nonlinear optical process, in which a UC material generates one high-energy photon for every two or more lowenergy excitation photons.…”
mentioning
confidence: 99%
“…Several examples have been reported in this sense. For instance Ji et al [19] reported about the fabrication of flexible arrays of resistive memory devices capable to be bent down to 3 mm without compromising their functionality. Other works [20,21] reported about flexible (high voltage) OTFT-based memory elements but in both cases the devices have been tested only with bending radii not smaller than 6 mm and 20 mm respectively.…”
Section: Introductionmentioning
confidence: 99%